The Potential of Highland Tropical Wheat As An Object Of Agroedutourism To Promote Tropical Wheat Development (Case study in Wates village, Getasan district, Semarang regency) - Kurnia, Theresa Dwi; Widyawati, Nugraheni Nugraheni; Prihtanti, Tinjung Mary (ASEAN Journal on Hospitality and Tourism, 2018)
The aims of this study are to know the potential of wheat farming in Getasan district as an object of agroedutourism and analyzed a wheat agroedutourism development strategy to support tropical wheat production. The collected data were analyzed using SWOT method. The results showed that wheat farmings in Getasan district was potentially become the object of agroedutourism. Strategies: Cooperation with governments, local farmers, investors, food companies to create an integrated agritourism involves the potential of cultural  tourism in the region; Create zoning for the various site locations required in agroedutourism; Plan an exciting and dynamic training program, special event, landscape arrangement, then promote it through various communication media; Improve managerial resources by establishing efficient structures, engaging in management training agritourism.